Hypothetical Learning Trajectory (HLT)-Based Learning Design Analysis - Rizka Fahruza Siregar; Rani Rahim; Rosmita Sari Siregar; Oktaviana Nirmala Purba (Universitas Suryakancana, 2026)
Mathematics learning trajectory is one of the key concepts in student-centered mathematics learning design. This article aims to analyze and describe the development of Hypothetical Learning Trajectory (HLT) as a framework for designing effective mathematics learning at the Junior High School level. The method used is design research with a qualitative approach through three phases: preparation phase, experimentation phase, and retrospective analysis phase. Research subjects consisted of 32 seventh-grade students at SMP Negeri 37 Medan. Research instruments included observation sheets, concept understanding tests, and semi-structured interviews. The results showed that HLT-based learning significantly improved students' conceptual understanding of integer material, with average scores increasing from 58.4 to 81.7. In addition, student learning motivation increased as demonstrated through the level of active participation in learning activities. The conclusions of this study confirm that systematic and reflective HLT development has great potential as an innovative strategy in meaningful and student-centered mathematics learning.